2017
DOI: 10.1111/tmi.12833
|View full text |Cite
|
Sign up to set email alerts
|

Birth prevalence of congenital talipes equinovarus in low‐ and middle‐income countries: a systematic review and meta‐analysis

Abstract: Abstractobjective Congenital talipes equinovarus (CTEV), or clubfoot, is a structural malformation that develops early in gestation. Birth prevalence of clubfoot is reported to vary both between and within low-and middle-income countries (LMICs), and this information is needed to plan treatment services. This systematic review aimed to understand the birth prevalence of clubfoot in LMIC settings.methods Six databases were searched for studies that reported birth prevalence of clubfoot in LMICs. Results were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 45 publications
2
71
0
1
Order By: Relevance
“…Although the authors made every attempt to identify and include contacts from every LMIC, it was not possible to do so, and this was also reflected in Shabtai et al ’s 10 study in 2014, which showed no evidence of Ponseti treatment in 80 countries. It is difficult to find accurate estimates of incidence of clubfoot for individual countries; we therefore used an incidence rate of 1.24/1000 births, based on a systematic review by Smythe et al 11 However, without more accurate incidence data, any estimates of expected numbers of cases may be flawed. A confounding factor to the growth in number accessing treatment over time documented in this report is that the number of survey respondents increased over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the authors made every attempt to identify and include contacts from every LMIC, it was not possible to do so, and this was also reflected in Shabtai et al ’s 10 study in 2014, which showed no evidence of Ponseti treatment in 80 countries. It is difficult to find accurate estimates of incidence of clubfoot for individual countries; we therefore used an incidence rate of 1.24/1000 births, based on a systematic review by Smythe et al 11 However, without more accurate incidence data, any estimates of expected numbers of cases may be flawed. A confounding factor to the growth in number accessing treatment over time documented in this report is that the number of survey respondents increased over time.…”
Section: Discussionmentioning
confidence: 99%
“…Data returned were collated and analysed using simple descriptive statistics to describe results from 2015 and compare with previous years. ‘Expected cases’ were calculated for every country and were defined as the number of children expected to be born with clubfoot in 2015, using an incidence rate of 1.24/1000 births 11 and the country’s population and birth rate as reported by the World Bank. 12 ‘Coverage’ was defined as the numbers of cases enrolled for treatment under the age of 1 year compared with the expected number of cases born in 2015.…”
Section: Methodsmentioning
confidence: 99%
“…1 Every year in Bangladesh an estimated 3500 -4000 children are born with a clubfoot deformity, with a global incidence of 1.5 per 1000 live births. 2 Untreated, clubfoot leads to lifelongdeformity causing individual disability and unproductivity. This causes the children to grow up as burdens of the family and ultimately leads to significant poverty.…”
Section: Introductionmentioning
confidence: 99%
“…This causes the children to grow up as burdens of the family and ultimately leads to significant poverty. 1 Armed Forces Medical College, Dhaka Cantonment, Dhaka, Bangladesh; 2 Rajshahi Medical College Hospital, Rajshahi, Bangladesh; 3 Department of Orthopaedic, Abdul Hamid Medical College, Kishorganj, Bangladesh; 4 Shahid Ziaur Rahman Medical College, Bogura, Bangladesh; 5 Chattogram Medical College Hospital, Chattogram, Bangladesh; 6 La Trobe University, Melbourne, Victoria, Australia 19,500 children with clubfoot were enrolled at WFL clinics across Bangladesh. 3 WFL is a charitable project of the Glencoe Foundation, with clinics appended to the Government of Bangladesh initiatives, and acknowledged by the Government as the National Clubfoot Programme in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Clubfoot, or congenital talipes equinovarus (CTEV), is one of the most common congenital musculoskeletal deformities. Within the Africa region, clubfoot birth prevalence is estimated as 1.11 (95%CI 0.96–1.26) per 1000 live births [ 1 ]. Untreated clubfoot results in pain, physical impairment and can ultimately cause disability [ 2 ].…”
Section: Introductionmentioning
confidence: 99%